2005
DOI: 10.1063/1.1853912
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties of ternary indides of type R2CoIn8 (R=Ce, Pr, and Dy)

Abstract: We have synthesized and investigated the magnetic and transport properties of a series of compounds, R 2 CoIn 8 (R = rare earth). Compounds form in single phase with a tetragonal structure (space group P4/mmm, no. 162). The Ce compound shows heavy fermion behavior. The magnetic susceptibility of Pr 2 CoIn 8 shows a marked deviation from the Curie-Weiss behavior at low temperatures, which is attributed to the crystalline electric field effects. Heat capacity and magnetization measurements show that Dy 2 CoIn 8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Apart from this, a high-pressure transport study is reported in the case of Ce 2 CoIn 8 [9]. We have reported on R 2 CoIn 8 (R = Ce, Pr and Dy) compounds [10]; Dy 2 CoIn 8 shows interesting magnetic properties and Pr 2 CoIn 8 shows crystal field effects.…”
Section: Introductionmentioning
confidence: 98%
“…Apart from this, a high-pressure transport study is reported in the case of Ce 2 CoIn 8 [9]. We have reported on R 2 CoIn 8 (R = Ce, Pr and Dy) compounds [10]; Dy 2 CoIn 8 shows interesting magnetic properties and Pr 2 CoIn 8 shows crystal field effects.…”
Section: Introductionmentioning
confidence: 98%